Prix des captifs, prix des esclaves : l’estimation du « prix de l’Homme » dans l’Antiquité tardive - Hervé Huntzinger (Les Cahiers de Framespa)
This paper opens on the assumption that, during Late Antiquity, the price of the slaves and the price of sold captives were quite similar. Latin, unlike ancient Greek, makes no distinction between the price of a slave and the ransom paid for a captive. Furthermore, the price of captives was generally the same as the ransom for comparable individuals. Moreover, this price remained stable on a large time scale, despite incomplete statistical series. There are, however, two exceptions to that. When dealing with fortunate individuals holding a high social position, their price increased significantly. On the contrary, when a huge amount of captives were sold, their price collapsed, as an evidence of the emergence of market laws. But, these laws only applied marginally and, as a result, could not hide that the estimated price of enslaved individuals and the price of freedom both had a symbolic aspect.